2023
DOI: 10.3389/fonc.2022.1065716
|View full text |Cite
|
Sign up to set email alerts
|

Baseline splenic volume as a biomarker for clinical outcome and circulating lymphocyte count in gastric cancer

Abstract: BackgroundThe spleen is the largest peripheral lymphoid organ in the body. Studies have implicated the spleen in the development of cancer. However, it is unknown whether splenic volume (SV) is associated with the clinical outcome of gastric cancer.MethodsData of gastric cancer patients treated with surgical resection were retrospectively analyzed. Patients were divided into three groups: underweight, normal-weight and overweight. Overall survival was compared in patients with high and low splenic volume. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…6 Zeng et al found baseline splenic volume to be correlated with peripheral immune cells (lymphocytes, NLR, CD4 + T cells, and natural killer cells) in patients with gastric cancer. 30 In addition, the spleen of patients with tumor develops differently after receiving diverse treatments. Recently, numerous studies have revealed that radiotherapy can cause changes in both the immune environment and splenic volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Zeng et al found baseline splenic volume to be correlated with peripheral immune cells (lymphocytes, NLR, CD4 + T cells, and natural killer cells) in patients with gastric cancer. 30 In addition, the spleen of patients with tumor develops differently after receiving diverse treatments. Recently, numerous studies have revealed that radiotherapy can cause changes in both the immune environment and splenic volume.…”
Section: Discussionmentioning
confidence: 99%
“…Early hematopoietic stem/progenitor cells in the spleen of a homozygous host are functionally altered and thus committed to the production of immunosuppressive myeloid cells 6 . Zeng et al found baseline splenic volume to be correlated with peripheral immune cells (lymphocytes, NLR, CD4 + T cells, and natural killer cells) in patients with gastric cancer 30 . In addition, the spleen of patients with tumor develops differently after receiving diverse treatments.…”
Section: Discussionmentioning
confidence: 99%